The Influence of Occupational Health and Safety (K3) and the Work Environment on Employee Performance at PT. Graha Humanindo Medan - Aftari, Nisa; Syafrizal, Syafrizal; Wibowo, M. Prasetyo (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This research is limited to the Occupational Health and Safety (K3) of the Company, especially regarding the work procedures implemented and also the Environment provided by PT. Graha Humanindo Medan has not been able to improve Employee Performance. The formulation of the problem in this study is whether the influence of company operational standards and company facilities on employee performance at PT. Graha Humanindo Medan. The purpose of this study is to determine the Effect of Occupational Health and Safety (K3) and the Work Environment on Employee Performance at PT. Graha Humanindo Medan. The population in this study amounted to 90 employees. This research approach is a quantitative approach. The testing method uses SPSS. Based on the results of testing and analysis, it shows that there is a positive and significant influence of the variables of Occupational Health and Safety (K3) and the Work Environment on employee performance.